VALUE ADDED TAX AS AN ECONOMIC CATEGORY AND OBJECT OF ACCOUNTING AND CONTROL - BOHATCHYK, Liudmyla; LOPATOVSKYI, Victor; BEZNOSKO, Karyna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The importance of the value-added tax in the formation of the revenue part of the state budget has been established. The main functions of VAT are analyzed from the point of view of managing the effectiveness of tax planning at the enterprise; the list of factors that increase and decrease the fiscal efficiency of VAT is summarized. The essence of the cost approach to the formation of the concept of "added value" was considered and it was proved that it cannot be used in the implementation of accounting and control procedures for VAT administration. An algorithm for calculating the VAT tax base has been created for accounting and control purposes. To improve the tax administration system, a list of VAT payers has been established at the enterprise; the procedure for applying tax rates to certain types of economic transactions is considered; the list of legal documents regulating the method of VAT accounting and control was analyzed. It was concluded that as an integral component of the cost of sold goods (works, services), VAT plays an important role in the formation of the enterprise’s pricing policy, and must be taken into account when analyzing price-forming factors. It has been proven that conducting a VAT study at an enterprise should be aimed at finding ways to increase its fiscal efficiency, which is achieved, first of all, through the construction of an effective system of electronic tax administration. And the leading role in this is played by constant monitoring of changes in the current legislation in the field of VAT calculation and payment. The importance of taking into account the VAT administration method during the analysis of price-forming factors and the construction of the marketing policy of the business entity is proven.